SOCIAL RESPONSIBILITY DISCLOSURE AND SUSTAINABLE DEVELOPMENT OF QUOTED INDUSTRIAL FIRMS IN NIGERIA (Journal of Global Accounting, 2023)
This study ascertained the relationship between social responsibility disclosure and sustainable development of quoted industrial firms in Nigeria. Fourteen (14) quoted industrial firms constituted the sample size of this study between 2011 and 2021. Ex-Post facto research design and content analysis were adopted while secondary data were extracted from the annual reports and accounts of the sampled firms and were analysed using E-Views 10.0 statistical software. The study employed descriptive statistics and inferential statistics using Pearson correlation and Binary Probit regression analysis. Three hypotheses were formulated and statistically tested at 5 per cent level of significance using regression analysis. Findings from the empirical analysis showed that a significant and positive relationship exists between environmental social responsibility disclosure and waste recycling (β1 = 0.829307; p-value = 0.0000
Keywords: Environmental Social Responsibility Disclosure; Ethical Social Responsibility Disclosure; Waste Recycling